EFFECT OF SHADING AND SPRAYING WITH SALICYLIC ACID ON THE PROPERTIES OF YIELD FOR TWO VARIETIES OF POTATO - Al-Mafriji, Othman K. A.; Al-Shammari, Loay M. K. (Journal of agricultural, environmental and veterinary sciences, 2017)
A field experiment was conducted during the agricultural season autumn 2016 in the experimental field of the Department of horticulture and landscaping in the college of Agriculture – University of Diyala, The study included three factors namely: - Two levels of shading (0%, 50%) by using green saran nets used for 42 day and four concentrations of salicylic acid (0, 50,100,150 mg.L-1) and two varieties of potatoes (Burren and Arizona. The experiment included 16 treatments for using the split – split plots Design system was applied according to the design of the complete random section of R.C.B.D and three replicates. The results showed superiority of plants shaded by 50% in the properties of the number of marketable tubers per plant and average wight of tuber marketable and overally yield and the percentage of protein in the tubers and reduce the content tubers of proline as it reached (9.05tuber.plant-1and 84.64gm and 55.84ton.h1 and 10.793% and 2.229 mg.gm-1) respectively. It was also outperformed treated plants in all concentrations of salicylic acid in the number of properties characterized by them treated plants concentration of 100 mg.L-1 at the best results for properties mentioned above as it reached (9.05tuber.plant-1and 89.56gm and 60.05ton.h-1and 11.084% and 1.869 mg.gm1), respectively. It was also outperformed of cultivar plants Arizona in properties mentioned above as it reached (8.61tuber.plant-1and 83.03gm and 52.98ton.h-1and 10.378% and 2.283mg.gm-1) respectively.
Keywords: Potato; Shading; Salicylic acid; Varieties; Heat stress; Salinity stress